Clinical aspects of tongue subgemmal neurogenous plaque: Surgical treatment of two symptomatic cases - Heguedusch, Daniele; Maciel, Luis Felipe Oliveira; Oliveira, Samanta Vicente; Custódio, Marcos; Nunes, Fabio Daumas; Lemos-Junior, Celso Augusto; Gallo, Camila de Barros (Journal of Oral Diagnosis, 2019)
Subgemmal neurogenous plaque (SNP) is a regional anatomic variation characterized by subepithelial nerve plexus and ganglion cells close to the taste buds at the posterolateral border of the tongue, and is usually asymptomatic. However, SNP may exhibit some diverse and non-specific clinical features that may challenge the diagnosis and, consequently, the appropriate management. We present two cases of papular and symptomatic lesions on the posterior lateral border of the tongue, which were diagnosed as SNP. The objective of this study is to report these two cases of SNP with a review of the clinical characteristics of SNP reported in the literature.